Language Attitude of Basa Osing Speakers in Banyuwangi - Ressi Maulidina Delijar; Hamamah Hamamah; Ika Nurhayani Nurhayani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This research aims to determine the language attitude of Basa Osing speakers. This research is important because of the debate over the Basa Osing linguistic status which considers that Basa Osing is only a variation of Javanese, and the other assumption that Basa Osing is an independent local language. The highlight of the debate was when the Governor of East Java removed Basa Osing from the curriculum of local content. It will affect the attitudes and behavior of Osing speakers, especially young speakers. This research used quantitative method and involved 100 participants around Banyuwangi. The instruments used to collect data were questionnaires. This research proved that there is decline of positive attitudes shown between generation to generation (group I score = 3.19, group 2 = 3.23, group 3 = 3.87). Basa Osing is very possible to experience language shifts in the future if the perspective of the society gets worse.